A NEW SPECIES OF FREZIERA (PENTAPHYLACACEAE) FROM ECUADOR, WITH LARGE LEAVES AND FLOWERS. (8th August 2016) - Santamaría-Aguilar, D.; Neill, D. A.; Lagomarsino, L. P.
Abstract : Freziera grandiflora (Pentaphylacaceae), a new species from western Ecuador with relatively large leaves, flowers and fruits, is described and illustrated. Its distribution, phenology, habitat and relationship to allied species are discussed. Its conservation status is tentatively considered Vulnerable.